Safty of home birth: perinatal mortality over a 3-year period in Germany - Christine Loytved (2007)
The reason why perinatal mortality seems to be higher in the home birth setting than in the birth centre setting has to be discussed. Especially home birth midwives have to follow the call of her client even in early pregnancy. As the number of perinatal mortality rates is quiet small in the different subgroups, we have to wait for the data of the following years. Those midwives in charge of constructing the documentation sheets for out-of-hospital births should make sure that the reasons be clearly stated why the midwife has to or wants to help at a preterm birth at home or in a birth centre. Summing up the results, at this point of our knowledge there is no need for midwives in Germany to advise primiparas to go to a birth centre instead of having a home birth. 1